Meta-Analysis of Empirical Estimates of Loss-Aversion - L. Brown Alexander; Taisuke Imai; Ferdinand M. Vieider; Colin Camerer (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Loss aversion is one of the most widely used concepts in behavioral economics. We conduct a large-scale interdisciplinary meta-analysis, to systematically accumulate knowledge from numerous empirical estimates of the loss aversion coefficient reported during the past couple of decades. We examine 607 empirical estimates of loss aversion from 150 articles in economics, psychology, neuroscience, and several other disciplines. Our analysis indicates that the mean loss aversion coefficient is between 1.8 and 2.1. We also document how reported estimates vary depending on the observable characteristics of the study design.
Keywords: D81; D90; C90; C11; 330; loss aversion; prospect theory; meta-analysis